KOMPOSISI FAMILI ASTERACEAE DI KAWASAN KEBUN KOPI DESA TOWEREN ANTARA KABUPATEN ACEH TENGAH - Alda Lolita; Muslich Hidayat; Aldilla Magfirah; Gebrina Rahmi; Mahmudahmi Mahmudahmi (Prosiding Seminar Nasional Biotik, 2022)
The Asteraceae family is one type of family that makes up herbaceous plant vegetation. Asteraceae is a family with high species diversity. This study aims to analyze the composition of the Asteraceae family in the coffee plantation area to determine the diversity index in the area. The research location is located in the coffee plantation area of Toweren Antara village, Central Aceh Regency. This research is a survey research with a quadratic method, the determination of the sample plot using purposive sampling technique. The data analysis technique uses the Shanon-Weinner formula, namely by finding the important value index, density value, frequency and dominance. The results showed that the composition of plant species in the Asteraceae family was found to be 11 species, the diversity of plant species in the Asteraceae family was categorized as moderate, namely = 1.884424. Diversity or the total INP level of the Asteraceae family in the coffee plantation area of 300% indicates the high category, the highest important value index is for the Gainsoga quadriradiata species with a value of 97.61%, while the lowest important value index is for the Galinsoga parviflora species with an INP value of 10.71%.